'I feel like I'm fighting fire': Teaching the young and educationally disadvantaged. (May 2022) - Yeo, Wan Ting; Tan, Aik Lim; Jamaludin, Azilawati
Abstract: This paper explores the emotional realities of teaching educationally disadvantaged students between the ages of 7 and 8 in Singapore. Data was collected via semi-structured face-to-face interviews with 9 primary school Mathematics teachers and analysed using inductive, grounded theory approach and thematic analysis. From a Conservation of Resources theory lens, findings show that educationally disadvantaged students are far from a homogeneous group as there is great diversity in the sources of disadvantage and obstacles to learning, contributing to the emotional weight borne by teachers of educationally disadvantaged students. Possible recommendations are also discussed. Highlights: Educationally disadvantaged children have a great diversity in the sources of disadvantages and obstacles to learning. In an inclusive classroom, teachers have to manage additional cognitive, developmental, and behavioural challenges. These factors add to the professional demands and the emotional weight borne by teachers.